Analysis of deaths following yeast-derived hepatitis B vaccination of infants, China, January 2013 to December 2020 - Zhang, Sihui; Zhao, Tianshuo; Chen, Linyi; Xie, Mingzhu; Lu, Qing-Bin; Du, Juan; Zeng, Jing; Huang, Ninghua; Liu, Yaqiong; Wang, Chao; Cui, Fuqiang (Frontiers in Public Health, 2023)
In China, adverse events following immunization (AEFI) are reported by the China AEFI Surveillance System (CNAEFIS). Serious AEFI, including deaths, are mandatorily reported and are evaluated for causality by province-or prefecture-level panels of experts. Yeast-derived HepB is the most widely used HepB in China for infants. However, the information about the death of infants caused by HepB is unclear. The CNAEFIS data on deaths following HepB from 2013 to 2020 were used for analyses. Descriptive analysis of epidemiologic characteristics was used to report death cases following HepB. We used administered doses to calculate denominators to estimate the risk of death after vaccination. During 2013–2020, there were 161 deaths following the administration of 173 million doses of HepB, for an overall incidence of 0.9 deaths per million doses. One hundred fifty-seven deaths were categorized as coincidental, and four deaths were accompanied by an abnormal reaction determined to be unrelated to the cause of death. The most common causes of death were neonatal pneumonia and foreign body asphyxia. These data provide reliable evidence on the safety of HepB among infants in China and can enhance public confidence in HepB immunization. To ensure public confidence in infants’ HepB vaccination, monitoring and scientifically evaluating AEFI-related deaths of HepB is necessary.